Violência na Escola:percepções de professores e alunos do ensino público e particular de São Leopoldo, RS - Simone Bicca Charczuk; Marcos Alencar Abaide Balbinotti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
Despite of the violence to be important investigation theme, they are still incipient the researches in which the school ambients is prioritized as place of manifestation of violent situations. In that side, the objective of that work was to investigate teachers and students' of São Leopoldo/RS perceptions concerning the theme. Three teachers and two students of a private school and three teachers and two students of a public school participated. An semi-structured interview was used to investigate the following aspects: occurrence of linked facts to the violence, concerns front to the occurrence of that phenomenon, conceptions (meanings) of violence in the school, generating factors of violence and forms used by the schools/students to face it. The data were submitted to the content analysis. The obtained data supply interpretative subsidies that can aid the elaboration of future proposed of investigation and intervention close to that context.